Use of Antiseptics and Antibiotics in Periimplant (Texas Journal of Multidisciplinary Studies, 2022)
Effective use of antibiotics is also recommended in orthopedic and traumatic surgery to prevent the spread of infection. In addition to this established system, a new approach to antibiotic prophylaxis can reduce infection. Antimicrobial prophylaxis is especially important in cases of open fractures.